Investment Knowledge in the Young Generation: A Theory of Reasoned Action Perspective - Rizka Aisyah Nurjannah; Firmansyah; Alfira (Global Research Collaboration, 2024)
This study aims to explore the investment knowledge of students from the Faculty of Economics and Business at Universitas Negeri Makassar using the Theory of Reasoned Action framework. Basic investment knowledge is crucial for prospective investors to avoid irrational investment practices, such as gambling, following trends without analysis, falling victim to fraud, and facing significant financial losses. Adequate knowledge, experience, and business instincts are essential for analyzing which assets to invest in within the capital market. Understanding the correct methods of investing is vital to minimize the risk of losses, particularly in stock market investments. While the growth of investors in Indonesia's capital market is promising, the overall interest in investing remains relatively low compared to other countries. This study underscores the importance of enhancing investment education to better prepare young investors. By increasing their financial literacy and decision-making capabilities, we can help foster a more robust investment culture and contribute to the financial well-being of the young generation.